Using of User Micro-Segmentation and Human Resource Management for Supply Chains Approaches to Study Prospective Target Audiences - V Vishnyakova; V Leonova; O Kulyamina (International Journal of Supply Chain Management, 2019)
Â Supply chain management can enable economies and companies to overcome disruptions and continually transform them to meet the changing needs and expectations of its customers, shareholders and other stakeholders. Therefore, the objective of this study was to investigate the influence of strategic human resource managing on supply chain resilience in manufacturing firms in Russia. The employed population is more considered to be economically active. Possibilities of consumption of this layer of the population are caused by a tendency of development of theories and practices about a society of consumption. The concept of earning in order to consume allows you to explore not only the possibility of consumption in terms of income of the employed population, but also the thematic direction of consumed economic benefits. Semantic fields that form a community of consumers among the employed population are formed by combining people working in one place. All these elements of one system can be described in the economic interpretation, which will allow to look at the new state of consumption of the employed population of the Russian Federation.